An imaging mass cytometry immunophenotyping panel for non-human primate tissues - Niewold, Paula; Ijsselsteijn, Marieke E.; Verreck, Frank A. W.; Ottenhoff, Tom H. M.; Joosten, Simone A. (Frontiers in Immunology, 2022)
It has recently become clear that spatial organization contributes to cellular function and that expanding our knowledge on cellular organization is essential to further our understanding of processes in health and disease. Imaging mass cytometry enables high dimensional imaging of tissue while preserving spatial context and is therefore a suitable tool to unravel spatial relationships between cells. As availability of human tissue collected over the course of disease or infection is limited, preclinical models are a valuable source of such material. Non-human primate models are used for translational research as their anatomy, physiology and immune system closely resemble those of humans due to close evolutionary proximity. Tissue from non-human primate studies is often preserved large archives encompassing a range of conditions and organs. However, knowledge on antibody clones suitable for FFPE tissue of non human primate origin is very limited. Here, we present an imaging mass cytometry panel development pipeline which enables the selection and incorporation of antibodies for imaging of non-human primate tissue. This has resulted in an 18-marker backbone panel which enables visualization of a broad range of leukocyte subsets in rhesus and cynomolgus macaque tissues. This high-dimensional imaging mass cytometry panel can be used to increase our knowledge of cellular organization within tissues and its effect on outcome of disease.